Ultrasonographic Findings in Patients with Benign and Malignant Thyroid Nodules who underwent Ultrasound Guided Fine Needle Aspiration Cytology - Majstorov, Venjamin (ID Design 2012/Scientific Foundation SPIROSKI, 2015)
Patients with thyroid nodules represent common problem in daily routine of thyroidologists as well as other medical specialties. Fortunately only small number of thyroid nodules turns out to be malignant. Ultrasound is most frequently used imaging modality in the evaluation of thyroid nodules and certain ultrasonographic features are associated with greater risk for malignancy.